2005
DOI: 10.1139/b05-065
|View full text |Cite
|
Sign up to set email alerts
|

The carbonic anhydrase gene families ofChlamydomonas reinhardtii

Abstract: Carbonic anhydrases (CAs) are zinc-containing metalloenzymes that catalyze the reversible interconversion of CO2 and HCO3–. Aquatic photosynthetic organisms have evolved different forms of CO2-concentrating mechanisms to aid Rubisco in capturing CO2 from the surrounding environment. One aspect of all CO2-concentrating mechanisms is the critical roles played by various specially localized extracellular and intracellular CAs. There are three evolutionarily unrelated CA families designated α-, β-, and γ-CA. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 57 publications
5
66
0
Order By: Relevance
“…CrCAH3 is associated with PSII, or is at least in its close vicinity under certain conditions (Pronina and Semenenko, 1984;Karlsson et al, 1998;Villarejo et al, 2002;Mitra et al, 2005). The catalytic site of water oxidation consists of a penta-m-oxo bridged tetramanganese calcium cluster (Mn 4 CaO 5 ) positioned within the OEC of PSII (Yano et al, 2006;Umena et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CrCAH3 is associated with PSII, or is at least in its close vicinity under certain conditions (Pronina and Semenenko, 1984;Karlsson et al, 1998;Villarejo et al, 2002;Mitra et al, 2005). The catalytic site of water oxidation consists of a penta-m-oxo bridged tetramanganese calcium cluster (Mn 4 CaO 5 ) positioned within the OEC of PSII (Yano et al, 2006;Umena et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…LCIB, located around the pyrenoid, traps CO 2 , either escaping from the pyrenoid or entering from outside the cell, into the stromal HCO 3 2 pool. This stromal HCO 3 2 pool then provides substrate to the pyrenoid thylakoid tubules for CAH3-catalyzed dehydration to CO 2 for Rubisco, as described in previous CCM models (Spalding et al, 1983b;Mitra et al, 2005;Spalding, 2008;Moroney et al, 2011).…”
Section: Co 2 Inhibition Of Lcia-mediated CI Uptakementioning
confidence: 97%
“…Immunoblot studies using antibodies raised against CAH3 demonstrated that CAH3 is associated with the thylakoid membrane (37). More specifically, immunolocalization studies indicated that CAH3 is localized on the luminal side of the thylakoids and inside the pyrenoid tubules (47). The evidence that CAH3 plays an essential role in the CCM is persuasive.…”
Section: Chlamydomonas Reinhardtii Ccmmentioning
confidence: 99%
“…CAH6 is a constitutively expressed ␤-CA in the chloroplast stroma (47,48). This CA might be involved in recapturing CO 2 as it effluxes from the thylakoid lumen and in helping to maintain a high concentration of inorganic carbon in the stroma.…”
Section: Chlamydomonas Reinhardtii Ccmmentioning
confidence: 99%